You are on page 1of 79

UNGKAPAN ALGEBRA I

UNGKAPAN ALGEBRA II
.

02/20/16

UNGKAPAN ALGEBRA III

Copyright Reserved

1

Permudahkan ungkapan
algebra yang berikut

a.) 2g – 5a + 3g
= 2g + 3g – 5a
= 5g – 5a

02/20/16

Sebutan serupa
Copyright Reserved

Sebutan tak
serupa

2

b.) w + 2u – 5w – 3u
= w – 5w + 2u – 3u
= - 4w

–u
c.) 5h + 1 + h + 9
= 5h + h + 1 + 9
= 6h + 10

02/20/16

Copyright Reserved

3

) 3a – 2b + 5a – 6b = 3a + 5a – 2b – 6b = 8a – 8b YEH….BERJAYA 02/20/16 Copyright Reserved 4 ..CUBA…… 1.)7X – 3Y – 2X – 2Y = 7X – 2X – 3Y – 2Y = 5X – 5Y 2.

a.12 c² 5 .) 3 a ( 3 b ) = 3a X 3b = 9 ab 02/20/16 Copyright Reserved d.) 2 ( .2a X -4b = 8 ab c.) – 4 c ( 3 c ) = .3b ) = 2 X -3b =-6b b.) – 2a ( .4b ) = .4 c X 3c = .

.12 w 2.) 5 ( .4 w ) = .) .5a ( .2 a ) = 10 a² YEH….3 w ) = .BERJAYA 02/20/16 Copyright Reserved 6 .Try u best 1.) 8b ( 3c ) = 24 bc 3.20 w 3.) 4w ( .

6. 6.3 Melakukan penambahan dan penolakan ke atas pecahan algebra.1•Memahami dan menggunakan konsep kembangan 6. x –y x+y 2 2 ) y 5 + .BAB 6 4 1 7y 3x – 15 3 (3x + 2)(5x – 1) Ungkapan Algebra III 6.(x ) y 3 8x + ( 02/20/16 Copyright Reserved X 2 + 1 2x + 8 2x – 5y 3 6 7 .2 •Memahami dan menggunakan konsep pemfaktoran ungkapan algebra untuk menyelesaikan masalah.4•Melakukan pendaraban dan pembahagian ke atas pecahan algebra.

6. a) .9x + 12y Copyright Reserved 8 .) satu ungkapan algebra dalam tanda kurung dengan satu sebutan algebra atau satu nombor Contoh : Kembangkan setiap yang berikut.3 ( 3x – 4y) = . a) -3x ( 3x – 4y) = .9x2 + 12xy 02/20/16 Mendarab setiap sebutan dalam tanda kurung dengan nombor atau sebutan di luar tanda kurung.1 Kembangan Ungkapan Algebra Kembangan ialah pendaraban a.

12xy a) 3x ( 3x – 4y) = 9x² .4y 3x .Contoh : 3x X 3x a) 3x ( 3x – 4y) = 9x² 3x .12xy 9 x² 3x X .12xy 02/20/16 Copyright Reserved 9 .4y = .

SOALAN 1 : 2 ( 3x – 5 ) 02/20/16 Copyright Reserved 10 .

SOALAN 2 : d ( e + 4d ) 02/20/16 Copyright Reserved 11 .

4m ( 2 – m ) 02/20/16 Copyright Reserved 12 .SOALAN 3 : .

3p ( p – 5q ) 02/20/16 Copyright Reserved 13 .SOALAN 4 : .

5x ( 2z – y – 3x ) 02/20/16 Copyright Reserved 14 .SOALAN 5 :.

SOALAN 6 : 2e ( 3e – f + 2g ) 02/20/16 Copyright Reserved 15 .

SOALAN : 02/20/16 Copyright Reserved 16 .

) dua ungkapan algebra dalam tanda kurung. Contoh 2 : Kembangkan setiap yang berikut. 17 .1 Kembangan Ungkapan Algebra b.3xy. b)(x – y) (3x + 5y) = x ( 3x + 5y ) –y ( 3x + 5y ) = 3x2 + 5xy .6.5y2 Sebutan serupa = 3x2 + 2xy – 5y2 02/20/16 Copyright Reserved Mendarab setiap sebutan dalam tanda kurung pertama dengan tiap-tiap sebutan dalam tanda kurung kedua.

Contoh 3 : (x – y) (3x + 5y) x -y 3x + 5y 3 x² +5xy .3 xy .5y² (x – y) (3x + 5y) = 3x² + 5xy – 3xy – 5y² = 3x² + 2xy – 5y² 02/20/16 Copyright Reserved 18 .

SOALAN 1 : ( x + 2 ) ( x + 3 ) 02/20/16 Copyright Reserved 19 .

SOALAN 2 : ( x – 3 ) ( x – 4 ) 02/20/16 Copyright Reserved 20 .

SOALAN 3 : ( 2x – 5 ) ( 3x + 2 ) 02/20/16 Copyright Reserved 21 .

SOALAN 4 : ( 3x – 4 ) ( 2x – 3 ) 02/20/16 Copyright Reserved 22 .

SOALAN 5 : ( 8 – e ) ( 2 + e ) 02/20/16 Copyright Reserved 23 .

SOALAN 6 : ( 5h – 3k ) ( 2h – k ) 02/20/16 Copyright Reserved 24 .

SOALAN 7 : ( 2x – 5y ) ( 2x + 3y ) 02/20/16 Copyright Reserved 25 .

SOALAN 8 : ( x + 5 )² = 02/20/16 Copyright Reserved 26 .

SOALAN 9 : ( 2x – 3 )² = 02/20/16 Copyright Reserved 27 .

SOALAN 10 : ( 3x – y )² = 02/20/16 Copyright Reserved 28 .

SOALAN : 02/20/16 Copyright Reserved 29 .

Rajah di bawah menunjukkan pelan ruang tamu rumah Encik Maniam. ( 2a – b) m ( a – 3b) m Hitung luas.Menyelesaikan Masalah yang Melibatkan Luas 1. dalam m². ruang tamu rumah Encik Maniam 02/20/16 Copyright Reserved 30 .

Hitung luas padang itu. ( 2y + 3) m ( y – 6) m 02/20/16 Copyright Reserved 31 . Sebuah padang sekolah berbentuk segi empat tepat yang berukuran ( y – 6 ) m panjang dan ( 2y + 3 ) m lebar.Menyelesaikan Masalah yang Melibatkan Luas 2.

Example 7: Find the product of (a + b)2. Method 1: (a + b)2 (a + b) means the square of (a + b) 2 = (a + b) (a +b) = a2 + ab + ba + b2 Like terms can be simplified = a2 + 2ab + b2 02/20/16 Method 2: Square the first term a.6. in the bracket (a + b)2 = a2 + (2 x a x b) + b2 = a2 + 2ab + b2 Compare the answers Copyright Reserved 32 . a and b + square the second term b. in the bracket + Multiply all the terms. 2.1 Expanding Brackets The expansion of two similar linear algebraic expressions can be found in the following methods.

b) means the square of (a .b) 2 = (a .2ab + b2 02/20/16 Method 2: Square the first term a. Method 1: (a .b) = a2 .b) (a . 2.1 Expanding Brackets The expansion of two similar linear algebraic expressions can be found in the following methods. in the bracket + Multiply all the terms.b)2 = a2 + (2 x a x -b) + -b2 = a2 .b)2 (a .ab . Example 8: Find the product of (a . in the bracket (a .ba + b2 Like terms can be simplified = a2 . a and -b + square the second term -b.6.b)2.2ab + b2 Compare the answers Copyright Reserved 33 .

2. in the bracket + Multiply the terms. in the bracket (2r + 3s)2 = (2r)2+ (2x2rx3s)+ (3s)2 = 4r2 +12rs + 9s2 Compare the answers Copyright Reserved 34 . 2r and 3s + square the second term 3s. Method 1: (2r + 3s)2 (2r + 3s) means the square of (2r + 3s) 2 = (2r + 3s) (2r + 3s) = 4r2 + 6rs + 6rs + 9s2 Like terms can be simplified = 4r2 + 12rs + 9s2 02/20/16 Method 2: Square the first term 2r.1 Expanding Brackets The expansion of two similar linear algebraic expressions can be found in the following methods.6. Example 9: Find the product of (2r + 3s)2.

1 Expanding Brackets The expansion of two similar linear algebraic expressions can be found in the following methods. Example 10: Find the product of (m – 2n)2. m and -2n + square the second term -2n.2mn + 4n2 Like terms can be simplified = m2 – 4mn + 4n2 02/20/16 Method 2: Square the first term m. 2. Method 1: (m – 2n)2 (m – 2n) means the square of (m – 2n) 2 = (m – 2n) (m – 2n) = m2 . in the bracket (m – 2n)2 = m2 + (2xmx-2n)+(-2n)2 = m2 .4mn + 4n2 Compare the answers Copyright Reserved 35 .2mn . in the bracket + Multiply the terms.6.

Three Identities That Must Be Remembered (a + b)2 = (a + b) (a + b) = a2 + 2ab + b2 (a .b) = a2 .b 2 = ( a + b ) ( a – b ) 02/20/16 Copyright Reserved 36 .b) (a .2ab + b2 a2 .b)2 = (a .

3p. 3. p. To find the factors of a term. and 3pq = p x 3q = q x 3p 02/20/16 Copyright Reserved 37 . = 3 x pq Thus.2 Factorisation of Algebraic Expressions Factors of a term is the number or terms that can divide a term exactly. 3q. As an example: 3pq state the term as a product of 3pq = 1 x 3pq two different terms first. the factors of 3pq = 1.6. q. pq.

6.2 Factorisation of Algebraic 9a andExpressions 3b can be Number 3 must be multiplied each term Factors of ato term is the in the bracket. As an example: Expand: 3(3a + b) = 9a + 3b Factorising is the reverse of expanding. divided by 3. So. 3 number termsfactor that is aor common of 9a + 3b can Factorise: = 9a + 3b = 3(3a + b) Expand 3(3a + b) 9a + 3b Factorise 02/20/16 Copyright Reserved 38 . divide a term exactly.

3c + 4) Taking out the common factor 2 02/20/16 Taking out the common factor a Copyright Reserved 39 . Example 1: Taking out the common factors of each term.2 Factorisation of Algebraic Expressions Factors of a term is the number or terms that can divide a term exactly.6. (a) 4ab2 – 6ac + 8a = 2(2ab2 – 3ac + 4a) = 2a(2b2 .

2 Factorisation of Algebraic Expressions Factors of a term is the number or terms that can divide a term exactly. Example 2: Factorise of the following.6. = 3(xy2 + 4x2y) Taking out the common factor 3 = 3xy(y + 4x) = 3x(y2 + 4xy) Taking out the common factor x 02/20/16 Taking out the common factor y Copyright Reserved 40 . (a) 3xy2 + 12x2y Taking out the common factors of each term.

Factorisation Of The Difference Between Two Squares.2 Factorisation of Algebraic Expressions Factors of a term is the number or terms that can divide a term exactly.6. Can you express some examples? x2 – y2 4a2 – b2 p2q2 – 16 9 – 25m2 1 – m2 02/20/16 x2 – ¼ 32 – x2y4 Copyright Reserved 41 .

(consists of two terms) The identity that must be remembered. x 2 – y2 = (x – y) (x + y) Example 1: Factorise of the following. 4a2 – b2 4a2 = (2a)2 = (2a)2 – b2 = (2a – b ) (2a + b) 02/20/16 Copyright Reserved 42 .6. Factorisation Of The Difference Between Two Squares.2 Factorisation of Algebraic Expressions Factors of a term is the number or terms that can divide a term exactly.

(consists of two terms) The identity that must be remembered. 1 = 12 1 – m2 = 12 – m2 = (1 – m ) (1 + m) 02/20/16 Copyright Reserved 43 .6. x 2 – y2 = (x – y) (x + y) Example 2: Factorise of the following.2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares.

(consists of two terms) The identity that must be remembered. 16 = 42 p2q2 = (pq)2 p2q2 – 16 = (pq)2 – 42 = (pq – 4 ) (pq + 4) 02/20/16 Copyright Reserved 44 .6. x 2 – y2 = (x – y) (x + y) Example 3: Factorise of the following. .2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares.

¼ = ( ½ )2 x2 – ¼ = x2 – ( ½ ) 2 = (x – ½ ) ( x + ½ ) 02/20/16 Copyright Reserved 45 . x 2 – y2 = (x – y) (x y) Example 4: + Factorise of the following.(consists of two terms) The identity that must be remembered. .2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares.6.

2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares. x 2 – y2 = Example (x – y) 5: (x Factorise + y) of the following.6. .(consists of two terms) The identity that must be remembered. 9 = 32 25m2 = (5m)2 9 – 25m2 = 32 – (5m)2 = (3 – 5m ) (3 + 5m) 02/20/16 Copyright Reserved 46 .

x 2 – y2 = (x – y) (x + y) Example 6: Factorise of the following.2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares. .(consists of two terms) The identity that must be remembered.6. 32 – x2y4 x2y4 = (xy2)2 = 32 – (xy2)2 = (3 – xy2 ) (3 + xy2) 02/20/16 Copyright Reserved 47 .

x2 – y2 = (x – y) (x + y) 36x2 = (6x)2 121y2 = (11y)2 Example 7: Factorise of the following. 36x2– 121y2 = (6x)2 – (11y)2 = (6x – 11y ) (6x + 11y) 02/20/16 Copyright Reserved 48 .2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares.6. .(consists of two terms) The identity that must be remembered.

(consists of two terms) The identity that must be remembered.2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares. x 2 – y2 Example 2 2 (x – y) (x + y) 8: a4 = (a= ) 4 4 a – b 4 2 2 Factorise of the following. . b = (b ) = (a2)2 – (b2)2 = (a2 – b2 ) (a2 + b2) = (a – b) (a + b) (a2 + b2) 02/20/16 Copyright Reserved 49 .6.

18 – 50y2 2 2 18 and 50 are not perfect squared.6.2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares. So.(consists of two terms) The identity that must be remembered. . 25y2 = (5y)2 = 2(9 – 25y2) = 2[32 – (5y)2] = 2(3 – 5y) (3 + 5y) 02/20/16 Copyright Reserved 50 . x –y – y) (x Example = 9: (x Factorise of + they) following. Taking out 2 as the common factors of each term.

2 Factorisation of Algebraic Expressions Factorisation Of The Difference Between Two Squares. x 2 – y2 = (x –10:y)Factorise (x + y)of the following.(consists of two terms) The identity that must be remembered. Example 16 = 42 a – 16 4 a4 = (a2)2 = (a2)2 – (22)2 = (a2 – 22 ) (a2 + 22) = (a – 2) (a + 2) (a2 + 4) 02/20/16 Copyright Reserved 51 .6.

2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of three terms. a) x2 + 10x + 25 b) x2 .y)2 Example 1: Factorise of the following.14x + 49 = x2 + 2(5x) + 52 = x2 . The identities that must be remembered.6.y) (x .2xy + y2 = (x . x2 + 2xy + y2 = (x + y) (x + y) = (x + y)2 x2 .2(7x) + 72 = (x + 5 )2 = (x .y) = (x .7)2 02/20/16 Copyright Reserved 52 .

x2 + 2xy + y2 = (x + y) (x + y) = (x + y)2 x2 .4xy + 4y2 = (3p)2 + 2(3pq) + q2 = x2 .y) = (x .y) (x .6.2(2xy) + (2y)2 = (3p + q)2 = (x – 2y)2 02/20/16 Copyright Reserved 53 .2xy + y2 = (x . The identities that must be remembered.y)2 Example 2: Factorise of the following. a) 9p2 + 6pq + q2 b) x2 .2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of three terms.

6. ax + ay + bx + by = (ax + ay) + (bx + by) = a(x + y) + b(x + y) Group the term with the same common factor Take out the common factor within the group = (a + b) (x + y) Taking out the common factor (x + y) 02/20/16 Copyright Reserved 54 .2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms. Example 1: Factorise of the following.

mn . 4m + 3n . Example 2: Factorise of the following.n) + 3(n .6.2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.mn) + (3n .12 = (4m .3) 02/20/16 Copyright Reserved 55 .12) = m(4 .n) (m .4) Group the term with the same common factor Take out the common factor within the group = m(4 – n) – 3(-n + 4) Taking out the common factor (4 – n) = (4 .

rs = (pq + qr) . pq + qr .2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.(ps + rs) = q(p + r) . Example 3: Factorise of the following.s) Group the term with the same common factor Take out the common factor within the group Taking out the common factor (p + r) 02/20/16 Copyright Reserved 56 .6.s(p + r) = (p + r) (q .ps .

5) + 3(4b . Example 4: Factorise of the following.5) (2a + 3) Group the term with the same common factor Take out the common factor within the group Taking out the common factor (4b – 5) 02/20/16 Copyright Reserved 57 .15 = (8ab – 10a) + (12b .15) = 2a(4b .2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.5) = (4b . 8ab – 10a + 12b .6.

y) – 3x(y – 9x) = 4(9x – y) + 3x(-y + 9x) = (4 + 3x) (9x – y) 02/20/16 Take out the common factor within the group Take out the common factor (9x – y) Copyright Reserved 58 . 36x – 4y – 3xy + 27x2 Group the term with the same common factor = (36x – 4y) .6. Example 5: Factorise of the following.2 Factorisation of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.(3xy – 27x2) = 4(9x .

Tips: 4+3=7 4 x 3 = 12 Change the expression into four terms x2 + 7x + 12 = x2 + 4x + 3x + 12 Group the term with the same common factor = (x2 + 4x) + (3x + 12) = x(x + 4) + 3(x + 4) = (x + 3) (x + 4) 02/20/16 Take out the common factor (x + 4) Copyright Reserved 59 .6.2 Factorisation Of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms. Example 6: Factorise of the following.

3 = 10 13x(-3) = .2 Factorisation Of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms. Example 7: Factorise of the following. Tips: 13 .39 Group the term with the same common factor = (x2 + 13x) .3x .6.(3x + 39) = x(x + 13) .39 = x2 + 13x .3(x + 13) = (x .39 Change the expression into four terms x2 + 10x .3) (x + 13) 02/20/16 Take out the common factor (x + 13) Copyright Reserved 60 .

Tips: 1-6=-5 1x(-6) = .(6a + 6) = a(a + 1) .6.6 = a2 + 1a – 6a .2 Factorisation Of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.6 Group the term with the same common factor = (a2 + a) . Example 8: Factorise of the following.6) (a + 1) 02/20/16 Take out the common factor (a + 1) Copyright Reserved 61 .6 Change the expression into four terms a2 – 5a .6(a + 1) = (a .

11 (-8)x(-3) = 24 Change the expression into four terms m2 – 11m + 24 = m2 – 8m – 3m + 24 Group the term with the same common factor = (m2 .8 .2 Factorisation Of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms.(3m .6. Tips: .8) 02/20/16 Take out the common factor (m .3(m .8m) .8) Copyright Reserved 62 .3 = .8) .3) (m .8) = (m .24) = m(m . Example 9: Factorise of the following.

6.2 Factorisation Of Algebraic Expressions Factorisation of algebraic expressions which consist of four terms. 2x4 = 8 Tips: 8+1=9 8x1=8 Change the expression into four terms 2x2 + 9x + 4 = 2x2 + 8x + 1x + 4 Group the term with the same common factor = (2x2 + 8x) + (1x + 4) = 2x(x + 4) + 1(x + 4) = (2x + 1) (x + 4) 02/20/16 Take out the common factor (x + 4) Copyright Reserved 63 . Example 10: Factorise of the following.

Can you give some examples? x2 y 3x – 2 y 02/20/16 numerator numerator Good job! numerator numerator numerator denominator denominator denominator denominator denominator  y2 – 4y + 4 y-2 Copyright Reserved 4a2 – b2 a+b x2 – 9 (x–3)(x-1) 64 .2 Factorising And Simplifying Algebraic Fractions Algebraic fractions are fractions with algebraic expressions as the numerator or denominator.6.

6.2

Factorising And Simplifying Algebraic Fractions

Algebraic fractions are fractions with algebraic
expressions as the numerator or denominator.
Example 1:
Simplify the given fraction.
Solution:

9ab2
3b
Congratulations!

3

1

=9xaxbxb
1
1
3xb
=3xaxb
1
= 3ab

02/20/16

Copyright Reserved

65

Factorising And Simplifying Algebraic Fractions

6.2

Algebraic fractions are fractions with algebraic
expressions as the numerator or denominator.
Example 2:
Well
Simplify the given fraction.
Solution:
done!
1
2

x –9
x+3

Factorise the
numerator first.

= (x – 3) (x 1+ 3)
x+3
=x-3
1
=x-3

02/20/16

Copyright Reserved

66

Factorising And Simplifying Algebraic Fractions

6.2

Algebraic fractions are fractions with algebraic
expressions as the numerator or denominator.
Example 3:
Simplify the given fraction.
Solution:

8 – 32m
2 - 8m
Factorise the
numerator and the
denominator first.

4

= 8 1(1 - 4m)
2 (1 - 4m)

Good Job!

1

= 4(1 – 4m)
1
1 - 4m
=4

02/20/16

Copyright Reserved

67

Example 4: Simplify the given fraction. 02/20/16 1 = 3p____ 3(2p – 3q) = p 2p – 3q ___ 1 ___ ____ Copyright Reserved 68 .Factorising And Simplifying Algebraic Fractions 6. Congratulations! Solution: 3p 6p – 9q Factorise the denominator first.2 Algebraic fractions are fractions with algebraic expressions as the numerator or denominator.

Solution: Bravo! 1 2 = (x + 3) (x + 2) x + 5x + 6 (x + 3)2 Factorise the numerator and the denominator first.Factorising And Simplifying Algebraic Fractions 6. 02/20/16 1 (x + 3) (x + 3) = x+2 x+3 Copyright Reserved 69 .2 Algebraic fractions are fractions with algebraic expressions as the numerator or denominator. Example 5: Simplify the given fraction.

Addition And Subtraction Of Algebraic Fractions 6.3 a) Adding or subtracting two algebraic fractions with similar denominators. Example 1: x + 4x 3 3 Good! 02/20/16 Solution: = x + 4x 3 = 5x 3 Copyright Reserved Maintain the denominator Add the numerator 70 .

6.3 Addition And Subtraction Of Algebraic Fractions a) Adding or subtracting two algebraic fractions with similar denominators. Solution: Example 2: 2x + y + 4x – 3y 2 2 = 2x + y + (4x-3y) 2 Maintain the denominator = 2x + 4x + y – 3y 2 Well done! = 6x – 2y 2 1 = 2 (3x –1y) 2 Add or subtract the numerators Simplify = 3x .y 02/20/16 Copyright Reserved 71 .

6.3 Addition And Subtraction Of Algebraic Fractions a) Adding or subtracting two algebraic fractions with similar denominators.6x x+2 Copyright Reserved 72 .9x – 7 x+2 x+2 = 3x .6x + 2 x+2 The positive term is always written in front 02/20/16 Maintain the denominator Add or subtract the numerators = 2 .9x .5 .(9x . Solution: Example 3: 3x .5 + 7 x+2 = .7) x+2 = 3x .5 .

3 Addition And Subtraction Of Algebraic Fractions b) Adding or subtracting two algebraic fractions with different denominators. Subtract the numerators Simplify Copyright Reserved 73 .3a 7 14 = 5a x 2 – 3a 7x2 14 = 10a – 3a 14 = 7a 14 Well Done! 02/20/16 = a 2 Let the denominators same.6. Solution: Example 1: 5a .

Solution: Example 2: m + n + 4m – 5n = n(m + n) + m(4m – 5n) mxn nxm Multiply the m n = mn + n + 4m .5mn mn 2 Very Good! 2 = 4m2 – 4mn + n2 mn numerator and the denominator Add or subtract the numerators = (2m – n) (2m – n) mn = (2m – n)2 mn 02/20/16 Copyright Reserved Simplify 74 .3 Addition And Subtraction Of Algebraic Fractions b) Adding or subtracting two algebraic fractions with different denominators.6.

(a) Denominator with one term Example 1: Example 2: 3 ( 4a – 5b) 4 ( 3m + 7n) y One term One term Solution: Solution: = 3 x 4a – 3 x 5b = 12a – 15b 02/20/16 Multiply the numerator separately = 4 x 3m + 4 x 7n y y = 12m – 28n y Copyright Reserved Multiply the numerator separately 75 .4 Multiplication And Division Of Algebraic Fractions Multiplying algebraic fractions.6.

(b) Denominator with two terms Example 4: Example 3: 4x – 8x2 x 15 5 4x X2 – y2 x x 2x x+y Two terms Two terms Solution: 1 1 = (x – y)(x + y) x x 1 1 2x (x+y) =x–y 2 02/20/16 Solution: 3 1 = 4x (1 – 2x) x 15 1 1 5 4x = 3(1 – 2x) = 3 – 6x Copyright Reserved 76 .4 Multiplication And Division Of Algebraic Fractions Multiplying algebraic fractions.6.

6. (a) Denominator with one term (b) Denominator with two terms. Example 1: Example 2: r ÷7 s 2s (a + b) ÷ 3(a + b) a2 – b2 a-b One term Solution: Two terms = r x 2s s 7 Solution: 1 = (a + b) x 1 1 = 2r 7 = 02/20/16 1 (a-b) (a-b)(a+b) 3(a + b) 1 3(a + b) Copyright Reserved 77 .4 Multiplication And Division Of Algebraic Fractions Dividing algebraic fractions.

4 Multiplication And Division Of Algebraic Fractions Dividing algebraic fractions. (b) Denominator with two terms Example 4: Example 3: 4(x – x2) ÷ (x-1) 5 5 3y2 ÷ y 2x 4x Two terms Two terms Solution: 2 2 y = 3y x 4x 2x 1 y 1 = 6y = 6y 1 02/20/16 Solution: = 4(x – x2) x 5 5 x-1 -1 1 = 4x(1– x) x 5 1 5 1 x-1 = .4x Copyright Reserved 78 .6.

Thank You 02/20/16 Copyright Reserved 79 .If at first you don't succeed ... so much for skydiving.